Near-infrared spectroscopy (NIRS) as an integrated approach for rapid classification and bioactive quality evaluation of intact Feronia limoni. Issue 1 (February 2021) - Yusnaini, R; Ikhsan, I; Idroes, R; Munawar, A A; Arabia, T; Saidi, N; Nasution, R
Abstract: Feronia limoni (Wood-apple) is one of the most researched plants containing bioactive compounds that have biological activity. So far, research on chemical compounds and fruit activity of F. limoni is often carried out using laboratory analysis, such as chromatographic analysis. This study aimed to assess the ability of NIRS to predict organic compounds contained in F. limoni based on its spectrum. Intact F. limoni samples were obtained from five different geographical origins in Aceh Province. Spectra data in form of absorbance spectrum were acquired using a portable sensing device NIRS instrument PSD FTNIRS i16 in wavenumbers 4000-10000 cm-1 or in the wavelength range from 1000 to 2500 nm with resolution windows of 0.02 nm and optical gain 4x. The results showed that NIRS was able to classify F. limoni samples based on geographical origins with the maximum explained variance of two PCs is 93%. Moreover, the respective wavelength related to this classification is 1090, 1270, 1390, 1459, 1602, 1713, 1912, and 2211 nm which corresponds to C-H, O-H, C-H-O, N-H stretching. It is related to acids, carbohydrates, and the fibre content of F. limoni samples from bent and stretched along the near-infrared region.